Comparative biology of the grenadiers Macrourus caml and M. whitsoni in the Ross Sea region, Antarctica - Moore, Bradley R.; Parker, Steven J.; Marriott, Peter M.; Sutton, Colin; Pinkerton, Matthew H. (Frontiers in Marine Science, 2022)
The grenadiers Macrourus caml and M. whitsoni form a significant bycatch component of fisheries for Antarctic toothfish (Dissostichus mawsoni) in the Southern Ocean. A lack of species-level biological and catch data has to date hindered the development of quantitative assessments for these deepwater species. This paper examines species- and sex-specific life histories of M. caml and M. whitsoni in the Ross Sea region, Antarctica, from samples collected from the commercial fishery and research collections between 2014 and 2021. Macrourus caml was found to live longer, grow slower, and attain a larger maximum length than M. whitsoni, reaching at least 65 years of age and 97 cm total length (TL) vs. 43 years and 78 cm TL for M. whitsoni. In addition, M. caml attains a larger length for a given age and a greater weight for a given length. For each species, females of a given age were larger and reached a greater maximum age than males. Assuming that selectivity of the fishing gear is related to fish size, greater fishing pressure on females than males is likely, and was evidenced by female-biased sex ratios of both species. Estimates of natural and fishing mortality rates were low for both species. Despite having a shorter lifespan and attaining a smaller maximum length, M. whitsoni matured later in life and at larger lengths than M. caml. Although sampling opportunities are constrained seasonally due to sea ice cover, gonad staging and interannual patterns in gonadosomatic indices suggest prolonged spawning for both species, with available data indicating peak spawning during austral summer. The differences in life history observed between these two closely related and morphologically similar species illustrates the importance of understanding species-specific life histories to infer responses to exploitation, provide key biological inputs to inform parameters for future risk assessments and ecosystem models as well as baseline information for comparative work over both time and space, contribute to greater clarity in managing fisheries that interact with these two species, and further our understanding of grenadier life history.